DEVELOPMENT OF CREATIVE ABILITIES OF YOUNGER SCHOOL STUDENTS - Asiljonova, Shahsanam (Журнал иностранных языков и лингвистики, 2021)
Project activity in human life plays a developmental role. This is especially important at primary school age, which is one of the most difficult and controversial periods of development in a person’s life for analysis. As part of the learning process at this age, the foundations of a person’s socialization are laid, the peculiarities of his interaction with others, and the educational base is formed, which will later become the foundation of his educational and work activities. All aspects of development at this age are subject to a qualitative restructuring, new psychological formations arise and form. In this regard, a creative approach to teaching in accordance with psychological characteristics, motivational preferences and tangible performance, which is so important for schoolchildren, is simply necessary.